Communication Skills of Health Personnel During Reproductive Ages in Pre-Conception Care - Fatemeh Ghaffari Sardasht; Nahid Jahani Shourab; Farzaneh Jafarnejad; Habibollah Esmaily (Guilan University of Medical Sciences, 2018)
Introduction: Suitable communication skills in pre-delivery cares are important due to the effect on the extent of anxiety and to better understand the training given. Objective: This study was conducted with the aim of determining the communication skills of health personnel during delivery of pre prenatal care. Materials and Methods: This cross-sectional study with analytical type was performed in 2012 and 2013 on 360 women who had visited healthcare centers in Mashhad to receive pre prenatal care along with 39 healthcare providers employed in these centers. The sampling was performed as multistage. The data collection instrument included the questionnaire of the characteristics of healthcare providers and research units as well as the checklist of assessing care based on Donabedian model. The data were analyzed using descriptive statistical indices as well as Kruskal-Wallis and Spearman statistical tests. Results: The results indicated that the communication skills of the personnel are of medium level. The minimum skill of the health personnel was observed in preserving the privacy of the service receivers. Other results also indicated that there is a significant relationship between the personnel s attitude toward necessity of prenatal cares (P=0.001) and their background in the plan of integrated cares for mothers (P=0.024). Conclusion: Based on the results, the minimum skill of health personnel was in preserving the privacy of the service receivers, so holding courses for communication skills is recommended for the health personnel.